Role of nutritional status and intervention in oesophageal cancer treated with definitive chemoradiotherapy: outcomes from SCOPE1 - Cox, S (Br J Cancer, 2016)
BACKGROUND: Malnutrition is common in oesophageal cancer. We aimed to identify nutritional prognostic factors and survival outcomes associated with nutritional intervention in the SCOPE1 (Study of Chemoradiotherapy in OesoPhageal Cancer with or without Erbitux) trial. METHODS: Two hundred and fifty eight patients were randomly allocated to definitive chemoradiotherapy (dCRT) +/− cetuximab. Nutritional Risk Index (NRI) scores were calculated; NRI<100 identified patients at risk of malnutrition. Nutritional intervention included dietary advice, oral supplementation or major intervention (enteral feeding/tube placement). Univariable and multivariable analyses using Cox proportional hazard modelling were conducted. RESULTS: At baseline NRI<100 strongly predicted for reduced overall survival (hazard ratio (HR) 12.45, 95% CI 5.24–29.57; P<0.001). Nutritional intervention improved survival if provided at baseline (dietary advice (HR 0.12, P=0.004), oral supplementation (HR 0.13, P<0.001) or major intervention (HR 0.13, P=0.003)), but not if provided later in the treatment course. Cetuximab patients receiving major nutritional intervention had worse outcomes compared with controls (13 vs 28 months, P=0.003). CONCLUSIONS: Pre-treatment assessment and correction of malnutrition may improve survival outcomes in oesophageal cancer patients treated with dCRT. Nutritional Risk Index is a simple and objective screening tool to identify patients at risk of malnutrition.